A water-soluble resin sand-consolidating agent and its preparation method and application
Through the use of water-soluble resin sand fixing agent and combined with raw materials such as resin matrix, the problem of difficult to take into account the consolidation strength and permeability of existing sand fixing agents under low temperature, medium and low mineralization water content conditions is solved, and the effect of taking into account high-strength sand fixing and high permeability is achieved, and the success rate of on-site operation of oil and water wells is improved.
Patent Information
- Application Number
- CN202411669060.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing sand-fixing agents are difficult to take into account both the consolidation strength and permeability under low temperature, medium and low mineralization water content, resulting in reduced production or sand production of oil wells, affecting the on-site effect and economic benefits.
A water-soluble resin sand fixing agent is used to form a high-strength solidified body through the combination of resin matrix, solubilizer, initiator, coupling agent, curing agent and enhancement additive, while maintaining a high permeability.
It achieves the effect of taking into account high-strength sand solidification and high permeability under low temperature, medium and low mineralization water content, and improves the on-site operation success rate of oil and water wells.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil well chemical sand control, and in particular to a water-soluble resin sand consolidating agent and a preparation method and application thereof. Background Art
[0002] In the middle and late stages of oilfield development, the injected water advances along the high permeability layer, the low permeability oil layer is repeatedly artificially fractured, and the sedimentary units of the oil layer are seriously flooded. The water content of the oil wells increases, and the oil wells are flooded prematurely. The reservoir has been washed by high-speed flow for a long time, and the sandstone skeleton structure has been destroyed. Not only is the deficit causing the casing damage wells to increase year by year, but the temperature of the oil layer has generally decreased. It is very important to solve the consolidation of reservoir sand under low temperature and medium-low mineralization water conditions, give full play to its supporting role, increase the reservoir seepage capacity, improve the production and injection effect of oil and water wells, and fundamentally prevent the sand problem.
[0003] At present, the sand-fixing agents used in oil wells mainly include jelly type, dispersion type, precipitation type, gel type and resin type. These types of sand-fixing agents have certain sand-fixing properties, but these sand-fixing agents have the following problems in practical application:
[0004] 1. After solidification, it has higher consolidation strength, but lower permeability;
[0005] 2. After solidification, the permeability is high, but the consolidation strength is low;
[0006] When the sand-fixing agent has the above problems, the oil and water wells either reduce production or produce sand, which greatly affects the on-site effect and economic benefits. To this end, the present invention proposes a water-soluble resin sand-fixing agent and a preparation method and application thereof. Summary of the invention
[0007] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a water-soluble resin sand consolidating agent and a preparation method and application thereof.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a water-soluble resin sand-consolidating agent, wherein the water-soluble resin sand-consolidating agent comprises the following raw materials in percentage by mass:
[0010] Resin matrix: 5-10%;
[0011] Solubilizer: 5-10%;
[0012] Initiator: 1-3%;
[0013] Coupling agent: 0.5-2%;
[0014] Curing agent: 0.2~0.5%;
[0015] Enhanced additives: 2-3%;
[0016] The balance is water.
[0017] Furthermore, the resin matrix is a water-based phenolic furan resin, and the water-based phenolic furan resin is XYH-FF900 water-based phenolic furan resin produced by Wuxi Xinyehao Chemical Co., Ltd.
[0018] Furthermore, the solubilizer is a low molecular weight glycidyl ether, and the low molecular weight glycidyl ether is one or a mixture of 1,6-adipic acid glycidyl ether and trimethylolpropane glycidyl ether.
[0019] Furthermore, the initiator is one or a mixture of porphyrin and quinolone aromatic compounds.
[0020] Furthermore, the coupling agent is one or a mixture of 2-hydroxyethyl methacrylate phosphate, bis(dioctyloxypyrophosphate)ethylene titanate, and distearoyloxyisopropylaluminate.
[0021] Furthermore, the curing agent is one or a mixture of lactic acid, benzoic acid and acrylic acid.
[0022] Furthermore, the reinforcing additive is one or a mixture of polyvinyl alcohol and polyvinyl formal.
[0023] In a second aspect, the present invention provides a preparation process of a water-soluble resin sand consolidating agent, comprising the following preparation process steps:
[0024] Step 1: weigh the raw materials according to the above mass percentage ratio, add the resin matrix, reinforcing additives and solubilizer into a first container with stirring, and stir and mix evenly;
[0025] Step 2: Add the initiator, coupling agent, curing agent and the remaining water into another stirring container, and stir to mix evenly;
[0026] Step 3: Pour the mixed liquid in the second container into the first container, stir and mix evenly to obtain a water-soluble resin sand-fixing agent.
[0027] Furthermore, in the step one, the mixture is stirred at a speed of 1000 to 2000 rpm for 30 to 60 minutes; in the step two, the mixture is stirred at a speed of 1000 to 2000 rpm for 5 to 10 minutes; and in the step three, the mixture is stirred at a speed of 1000 to 2000 rpm for 10 to 20 minutes.
[0028] In the third aspect, the present invention proposes the use of a water-soluble resin sand-fixing agent in the sand-fixing construction of oil wells, water wells or gas wells in loose sandstone reservoirs that are prone to sand production. The suitable formation temperature is 35-150°C. When used, the water-soluble resin sand-fixing agent is injected into the target layer with a pump truck, and after the well is shut down, it solidifies for 1-3 days before normal production.
[0029] The present invention has the following technical effects:
[0030] The sand-fixing agent of the present invention is water-soluble, and after solidification, it is tightly combined with the formation sand and soil, and has high consolidation strength and high permeability, that is, it can fix the sand with high strength while maintaining high permeability of the oil layer, and can greatly improve the success rate of on-site operations of oil and water wells. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0032] Example 1: A preparation process of a water-soluble resin sand-fixing agent proposed in the present invention is as follows: 10 g of water-based phenolic furan resin, 4 g of polyvinyl alcohol and 10 g of 1,6-diglycol ether are added to a first container, and the mixture is stirred at a speed of 1000 rpm for 30 minutes; 2 g of quinolone aromatic compound, 1 g of bis(dioctyloxypyrophosphate)ethylene titanate, 0.4 g of benzoic acid and 172.6 g of water are added to another second container, and the mixture is stirred at a speed of 1000 rpm for 5 minutes; the mixed solution in the second container is poured into the first container, and the mixture is stirred at a speed of 1000 rpm for 10 minutes to obtain a water-soluble resin sand-fixing agent.
[0033] The sand consolidating agent prepared in this embodiment has an initial viscosity of 4.6 mPa·s after testing.
[0034] The sand consolidating agent prepared in this embodiment, the pressure plugging experiment: take a sand filling tube with a length of 30cm and a diameter of 25mm, fill it with 280-320 mesh fine sand, fill it tightly, and measure the permeability to be 2.0μm 2 . Slowly inject the prepared sand consolidation agent into the sand filling pipe. When the sand consolidation agent flows out from the outlet, stop pumping. Seal both ends of the sand filling pipe, heat to 60℃ for 48h, and after cooling to room temperature, the permeability is measured to be 1.82μm. 2 , the permeability retention rate reached 91%. The compressive strength was measured to be 6.7MPa.
[0035] Example 2: A preparation process of a water-soluble resin sand-fixing agent proposed in the present invention is as follows: 13 g of water-based phenolic furan resin, 4 g of polyvinyl alcohol and 10 g of 1,6-diglycol ether are added to a first container, and the mixture is stirred at a speed of 1000 rpm for 30 minutes; 3 g of quinolone aromatic compound, 2 g of bis(dioctylpyrophosphate)ethylene titanate, 0.4 g of benzoic acid and 167.6 g of water are added to another second container, and the mixture is stirred at a speed of 1000 rpm for 5 minutes; the mixed solution in the second container is poured into the first container, and the mixture is stirred at a speed of 1000 rpm for 10 minutes to obtain a water-soluble resin sand-fixing agent.
[0036] The sand consolidating agent prepared in this embodiment has an initial viscosity of 7.1 mPa·s after testing.
[0037] The sand consolidating agent prepared in this embodiment, the pressure plugging experiment: take a sand filling tube with a length of 30cm and a diameter of 25mm, fill it with 280-320 mesh fine sand, fill it tightly, and the permeability is measured to be 1.91μm 2 . Slowly inject the prepared sand consolidation agent into the sand filling pipe. When the sand consolidation agent flows out from the outlet, stop pumping. Seal both ends of the sand filling pipe, heat to 60℃ for 48h, and after cooling to room temperature, the permeability is measured to be 1.643μm 2 , the permeability retention rate reached 86%. The compressive strength was measured to be 9.8MPa.
[0038] Example 3: A preparation process of a water-soluble resin sand-fixing agent proposed in the present invention is as follows: 16 g of water-based phenolic furan resin, 4 g of polyvinyl alcohol and 10 g of solubilizer 1,6-diglycol ether are added to a first container, and the mixture is stirred at a speed of 1000 rpm for 30 minutes; 4 g of quinolone aromatic compound, 3 g of bis(dioctyloxypyrophosphate)ethylene titanate, 0.4 g of benzoic acid and 162.6 g of water are added to another second container, and the mixture is stirred at a speed of 1000 rpm for 5 minutes; the mixed solution in the second container is poured into the first container, and the mixture is stirred at a speed of 1000 rpm for 10 minutes to obtain a water-soluble resin sand-fixing agent.
[0039] The sand consolidating agent prepared in this embodiment has an initial viscosity of 7.1 mPa·s after testing.
[0040] The sand consolidating agent prepared in this embodiment, the pressure plugging experiment: take a sand filling tube with a length of 30cm and a diameter of 25mm, fill it with 280-320 mesh fine sand, fill it tightly, and the permeability is measured to be 1.91μm 2 . Slowly inject the prepared sand consolidation agent into the sand filling pipe. When the sand consolidation agent flows out from the outlet, stop pumping. Seal both ends of the sand filling pipe, heat to 60℃ for 48h, and after cooling to room temperature, the permeability is measured to be 1.643μm2 , the permeability retention rate reached 86%. The compressive strength was measured to be 9.8MPa.
[0041] Example 4: A preparation process of a water-soluble resin sand-fixing agent proposed in the present invention is as follows: 20 g of water-based phenolic furan resin, 4 g of polyvinyl alcohol and 10 g of 1,6-diglycol ether are added to a first container, and the mixture is stirred at a speed of 1000 rpm for 30 minutes; 5 g of quinolone aromatic compound, 4 g of bis(dioctyloxypyrophosphate)ethylene titanate, 0.4 g of benzoic acid and 156.6 g of water are added to another second container, and the mixture is stirred at a speed of 1000 rpm for 5 minutes; the mixed solution in the second container is poured into the first container, and the mixture is stirred at a speed of 1000 rpm for 10 minutes to obtain a water-soluble resin sand-fixing agent.
[0042] The sand consolidating agent prepared in this embodiment has an initial viscosity of 7.1 mPa·s after testing.
[0043] The sand consolidating agent prepared in this embodiment, the pressure plugging experiment: take a sand filling tube with a length of 30cm and a diameter of 25mm, fill it with 280-320 mesh fine sand, fill it tightly, and the permeability is measured to be 1.98μm 2 . Slowly inject the prepared sand consolidation agent into the sand filling pipe. When the sand consolidation agent flows out from the outlet, stop pumping. Seal both ends of the sand filling pipe, heat to 60℃ for 48h, and after cooling to room temperature, the permeability is measured to be 1.624μm 2 , the permeability retention rate reached 82%. The compressive strength was measured to be 12.6MPa.
[0044] As can be seen from Examples 1-4, increasing the dosage of resin, initiator and coupling agent significantly increases the compressive strength of the final consolidated body, but the permeability also shows a downward trend. During the on-site construction process, it is required that the stratum can retain sufficient strength of 8MPa after consolidation, and at the same time, the damage to the permeability of the stratum should be lower, and the permeability retention rate should be more than 85%. Therefore, it is recommended to adjust the dosage of resin, initiator and coupling agent in time according to the sand production degree and output of different wells on site to achieve the best implementation effect.
[0045] Example 5: A preparation process of a water-soluble resin sand-fixing agent proposed in the present invention is as follows: 15 g of water-based phenolic furan resin, 6 g of polyvinyl formal and 15 g of trimethylolpropane glycidyl ether are added into a container, and the mixture is stirred at a speed of 1500 rpm for 40 minutes; 3 g of porphyrin aromatic compound, 1.5 g of 2-hydroxyethyl methacrylate phosphate, 0.6 g of lactic acid and 158.9 g of water are added into another second container, and the mixture is stirred at a speed of 1500 rpm for 8 minutes; the mixed solution in the second container is poured into the first container, and the mixture is stirred at a speed of 1500 rpm for 15 minutes to obtain a water-soluble resin sand-fixing agent.
[0046] The sand consolidating agent prepared in this embodiment has an initial viscosity of 6.3 mPa·s after testing.
[0047] The sand consolidation agent prepared in this example, pressure plugging experiment: take a sand filling tube with a length of 30cm and a diameter of 25mm, fill it with 380-420 mesh fine sand, and fill it tightly. The measured permeability is 1.13μm 2 . Slowly inject the prepared sand consolidation agent into the sand filling pipe. When the sand consolidation agent flows out from the outlet, stop pumping. Seal both ends of the sand filling pipe, heat to 60℃ for 48h, and after cooling to room temperature, measure the permeability to be 0.98μm. 2 , the permeability retention rate reached 87%. The compressive strength was measured to be 9.8MPa.
[0048] Example 6: A preparation process of a water-soluble resin sand-fixing agent proposed in the present invention is as follows: 20 g of water-based phenolic furan resin, 6 g of polyvinyl formal and 20 g of trimethylolpropane glycidyl ether are added into a container, and the mixture is stirred at a speed of 2000 rpm for 60 minutes; 6 g of quinolone aromatic compound, 4 g of distearoyloxyisopropylaluminate, 1 g of acrylic acid and 143 g of water are added into another second container, and the mixture is stirred at a speed of 2000 rpm for 10 minutes; the mixed solution in the second container is poured into the first container, and the mixture is stirred at a speed of 2000 rpm for 20 minutes to obtain a water-soluble resin sand-fixing agent.
[0049] The sand consolidating agent prepared in this embodiment has an initial viscosity of 8.2 mPa·s after testing.
[0050] The sand consolidating agent prepared in this embodiment, pressure plugging experiment: take a sand filling tube with a length of 30cm and a diameter of 25mm, fill it with fine sand with a ratio of 280-320 mesh: 380-420 mesh = 1:1, and fill it tightly. The measured permeability is 1.38μm 2 . Slowly inject the prepared sand consolidation agent into the sand filling pipe. When the sand consolidation agent flows out from the outlet, stop pumping. Seal both ends of the sand filling pipe, heat to 60℃ for 48h, and after cooling to room temperature, the permeability is measured to be 1.17μm.2 , the permeability retention rate reached 85%. The compressive strength was measured to be 11.3MPa.
[0051] It can be seen from Examples 1-6 that, within the scope of the patent requirements, by adjusting the types of coupling agent, initiator, enhancer, and solubilizer, the strength of the formed solid body is above 5 MPa, and the permeability retention rate is above 80%.
[0052] Comparative example: The compressive strength of the sand consolidating agent prepared indoors according to Example 1 of CN 115572592 A is 5.8 MPa, and the permeability retention rate is 73%. The strength of the sand consolidating agent prepared indoors according to the example provided by CN 102838975 A is 7.2 MPa, and the permeability retention rate is 62%.
[0053] It can be seen that the sand consolidation agent preparation method provided in this application has significant advantages in compressive strength and permeability.
[0054] The resin matrix, initiator, curing agent and reinforcing additive of the water-soluble sand consolidating agent of the present application react with each other in the formation to form a networked high-strength resin structure. Under the action of the coupling agent, the resin structure is fully combined with the surface of the sand particles in the formation to form a high-strength consolidated body. After the reaction, the solubilizing agent and water will gradually precipitate, so the consolidated formation still retains a relatively high permeability.
[0055] Specifically, the resin matrix and the curing agent react with each other at a temperature of 35℃-120℃ and under the action of the initiator to form a polymer network space resin, which forms a high-strength resin structure with the reinforcing additive; the organic group of the coupling agent reacts with the resin structure, and the ester group reacts with the hydroxyl group on the surface of the sand grains to hydrolyze, thereby firmly combining the resin with the space network structure with the formation sand grains with chemical bonds to form a high-strength consolidation body, which prevents the migration of sand grains and the formation from sanding. The solubilizer and water do not participate in the reaction and will eventually precipitate gradually. The two occupy more than 70% of the sand consolidation agent formula. After precipitation, the consolidation body forms a large number of pores, so the formation after consolidation still retains a high permeability.
[0056] The water-soluble sand-fixing agent sand-control technology of this application has been applied to more than 500 wells, and has been applied in Shengli oil production plants, CNOOC, Liaohe, Dagang, Western Oil Region, and some foreign blocks. The average daily increase in liquid in the applied wells is 23%, and the daily increase in oil is 35%. After sand control, the average effective period of oil and water wells has increased from 200 days to more than 400 days; the sand-fixing agent of this application has no solid phase before solidification, and it is easy to enter the formation to effectively block the water-producing layer. The dispersed sand has high consolidation strength and good permeability after consolidation. Its technical advantages are mainly:
[0057] 1. The viscosity of the sand consolidating agent itself is lower than 10mPa·s;
[0058] 2. The consolidation strength of the sand consolidating agent is between 5MPa and 15MPa, and the permeability retention rate is more than 80%;
[0059] 3. Consolidation effect can only be produced after encountering stratum sand, which is beneficial to construction safety;
[0060] 4. The sand consolidating agent does not solidify at room temperature of 25°C, the lowest reaction temperature is 35°C, and the highest temperature resistance is 150°C;
[0061] 5. It is easy to use and reliable, and the solidification time is 1-3 days, which is easy to control.
[0062] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A water-soluble resin sand consolidating agent, characterized in that: The water-soluble resin sand consolidating agent comprises the following raw materials in percentage by mass: Resin matrix: 5-10%; Solubilizer: 5-10%; Initiator: 1-3%; Coupling agent: 0.5-2%; Curing agent: 0.2~0.5%; Enhanced additives: 2-3%; The balance is water; The resin matrix is a water-based phenolic furan resin; The solubilizing agent is a low molecular weight glycidyl ether; The initiator is one or a mixture of porphyrins and quinolone aromatic compounds; The coupling agent is one or a mixture of 2-hydroxyethyl methacrylate phosphate, bis(dioctyloxypyrophosphate)ethylene titanate, and distearoyloxyisopropylaluminate; The curing agent is one or a mixture of lactic acid, benzoic acid and acrylic acid; The reinforcing additive is one or a mixture of polyvinyl alcohol and polyvinyl formal; The low molecular weight glycidyl ether is one of 1,6-adipic acid glycidyl ether and trimethylolpropane glycidyl ether or a mixture of several thereof.
2. A process for preparing the water-soluble resin sand consolidating agent according to claim 1, characterized in that: The preparation process comprises the following steps: Step 1: weigh the raw materials according to the above mass percentage ratio, add the resin matrix, reinforcing additives and solubilizer into a first container with stirring, and stir and mix evenly; Step 2: Add the initiator, coupling agent, curing agent and the remaining water into another stirring container, and stir to mix evenly; Step 3: Pour the mixed liquid in the second container into the first container, stir and mix evenly to obtain a water-soluble resin sand-fixing agent.
3. The preparation process of the water-soluble resin sand consolidating agent according to claim 2, characterized in that: In the step 1, the mixture is stirred at a speed of 1000 to 2000 rpm for 30 to 60 minutes; in the step 2, the mixture is stirred at a speed of 1000 to 2000 rpm for 5 to 10 minutes; in the step 3, the mixture is stirred at a speed of 1000 to 2000 rpm for 10 to 20 minutes.
4. An application of a water-soluble resin sand consolidating agent, characterized in that: The water-soluble resin sand consolidating agent according to claim 1 is used in the sand consolidation construction of oil wells, water wells or gas wells in loose sandstone reservoirs prone to sand production, and is suitable for formation temperatures of 35 to 150°C.
Citation Information
Patent Citations
Sand-proof consolidation agent
CN102838975A
Thin oil well sand consolidation agent and preparation method thereof
CN115572592A
Low-density foam resin sand preventing agent suitable for sand production horizontal well of unconsolidated sandstone reservoir and preparation method of low-density foam resin sand preventing agent
CN106634920A
Water-based furan resin sand-consolidation main agent, preparation method thereof and sand-consolidation agent
CN110117347A
Cited By
Loose sandstone oil reservoir sand control agent and preparation method and application thereof
CN122878935A